Application of a specific clinical pathway can affect the choice of trial of labor in patients with a history of cesarean delivery - Petra Psenkova; Miroslav Tedla; Lenka Minarcinova; Jozef Zahumensky (BMC, 2024)
Abstract Background Mode of delivery in women with previous history of cesarean delivery (CD) is highly modifiable by the practices of the delivery unit. Vaginal birth after a cesarean (VBAC) delivery is a safe and preferred alternative in most cases. The aim of this study was to assess the impact of adopting a complex set of measures aimed at the mode of delivery in this group. Methods This was a retrospective observational study comparing two birth cohorts before and after the implementation of a series of quality improvement (QI) interventions. The study cohorts comprised women with a history of cesarean delivery who gave birth in the period before (January 2013 - December 2015) and after (January 2018 - December 2020) the adoption of the QI measures. The measures were focused on singleton term cephalic pregnancies with a low transverse incision in the uterus. Measures included approval of all planned CDs by a senior obstetrician, re-training staff on the use of the FIGO classification for intrapartum fetal cardiotocogram, establishing VBAC management guidelines, encouraging epidural analgesia during trial of labor after cesarean (TOLAC), establishing a labor ward team and introducing a monthly maternity audit. Results Term singleton cephalic pregnancies with previous history of CD accounted for 12.55% of all births in the pre-intervention period and 12.01% in the post-intervention period. The frequency of cesarean deliveries decreased from 89.94% in the pre-intervention period to 64.47% in the post-intervention period (p < 0.0001). We observed a significant increase in TOLAC from 13.18 to 42.12% (p<0.0001) and also an increase in successful VBAC from 76.27 to 84.35% (p < 0.0001). All changes occurred without statistically significant change in overall perinatal mortality. Conclusions This study demonstrates the feasibility to safely increase trial of labor and vaginal birth after cesarean delivery by implementing a series of quality improvement interventions and clinical pathway changes.